Upaya Peningkatan Keterampilan Berbicara melalui Media Cerita Gambar Seri pada Anak Usia Dini 5-6 Tahun di TK Mawar Indah T.A 2018/2019 - Ruth Donda E. Panggabean; Rahmi Wardah Ningsih; Hotnita Ezra Naibaho (Journal on Education, 2023)
This research aims to improve speaking skills through the media series of picture series in early 5-6 years old children in TK Mawar Indah School Years 2018/2019. Speaking skills can be seen from the courage to speak, fluency in speaking and retelling in sequence according to the contents of the picture. This type of research uses classroom action research (CAR) or the English term Classroom Action Research (CAR). Subjects in this study were B2 group children with 20 children consisting of 9 girls and 11 boys. Data collection techniques in this study using the method of observation and documentation. From the results of the study showed that the media image series can improve speaking skills in early childhood 5-6 years in kindergarten Mawar Indah. This can be seen from the results of the research. In the first cycle there were 9 children or 45% with criteria for developing as expected (BSH), and 11 children or 55% with criteria for developing (MB). In cycle II there were 17 children or 85% with criteria for developing as expected (BSH), and 4 children or 15% with criteria for developing (MB).